Application of Interval Training to the Vo2MAX of Futsal Extracurricular Participants - Sulaeman, Maman; Nur, Hana Astria (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The objective of this research is to ascertain the VO2max of futsal extracurricular participants at SMA 1 Kadugede by utilizing interval training. Materials and Methods. The Purvosive sampling technique was employed to select samples from the population of pupils at SMA Negeri 1 Kadugede, and the research method employed was an experiment with a One-Group Pretest Posttest design. The Bleep Test is employed to monitor the development of maximal oxygen return, and the data will be analyzed using the normality test. Results. Vo2Max increases significantly in extracurricular futsal participants of SMAN 1 Kadugede as a result of interval training. Conclusion. The analysis of the research data has yielded the conclusion that interval training can enhance the VO2MAX capacity of futsal extracurricular participants. The author evaluated the increase in cardiovascular endurance of participants using the interval training approach, which has positive implications for their futsal performance. It has been demonstrated that this procedure is effective in enhancing the aerobic capacity of players.